Creative Speaking in Foreign Language Learning Systematic Literature - Ernawati; Muhammad Samsul Ulum; M. Faishol (Asalibuna, 2025)
Creative speaking is an essential component of foreign language learning because it strengthens linguistic flexibility, communicative confidence, and the quality of spoken language production. Nevertheless, classroom practices remain dominated by conventional methods that offer limited opportunities for learners to explore language creatively. This study aims to identify the urgency of speaking creativity, pedagogical solutions proposed in recent literature, and the benefits gained in foreign language learning contexts. Using a Systematic Literature Review (SLR) following Kitchenham’s (2004) guidelines, reputable scientific articles published between 2020 and 2025 were reviewed from Scopus, ScienceDirect, ERIC, and Web of Science databases. Of the 122 articles initially found, 23 met the inclusion criteria based on the PRISMA flow and were analyzed in depth. Findings reveal three central characteristics of speaking creativity research: (1) task design and contextual support, including digital storytelling, CLIL, social media–based interaction, and collaborative speaking tasks; (2) cognitive and psychological dimensions, such as divergent thinking, cognitive flexibility, motivation, and personality factors; and (3) pedagogical and collaborative innovations, including performative learning, technology-enriched instruction, and plurilingual approaches. Analysis of RQ1 demonstrates that creative speaking is crucial for improving fluency, coherence, accuracy, and communicative effectiveness. RQ2 indicates that creative pedagogical solutions arise through innovative task design, digital tool integration, and supportive collaborative learning environments. RQ3 confirms that speaking creativity contributes significantly to linguistic development, cognitive growth, affective engagement, and 21st-century skills, particularly critical thinking and problem solving. This study concludes that speaking creativity is a core foundation in modern language education and must be integrated through adaptive and innovative pedagogical strategies. Practical implications are offered for teachers, researchers, and curriculum designers to foster creative expression, collaboration, and effective communicative performance in global language learning.   Abstrak:  Keterampilan berbicara kreatif merupakan komponen penting dalam pembelajaran bahasa asing karena mampu meningkatkan keluwesan berbahasa, kepercayaan diri berkomunikasi, serta kualitas produksi bahasa lisan. Namun, praktik pembelajaran di kelas masih didominasi pendekatan konvensional yang kurang memberikan ruang bagi eksplorasi kreatif peserta didik. Penelitian ini bertujuan memetakan urgensi kreativitas berbicara, solusi pedagogis yang ditawarkan dalam literatur terbaru, serta manfaat yang diperoleh dalam konteks pembelajaran bahasa asing. Dengan menggunakan metode Systematic Literature Review (SLR) berdasarkan pedoman Kitchenham (2004), penelitian ini menelaah artikel ilmiah bereputasi yang terindeks Scopus, ScienceDirect, ERIC, dan Web of Science, yang dipublikasikan antara tahun 2020 hingga 2025. Dari 122 artikel yang teridentifikasi, melalui proses seleksi PRISMA, diperoleh 23 artikel yang memenuhi kriteria inklusi dan dianalisis secara mendalam. Hasil penelitian menunjukkan bahwa kajian mengenai kreativitas berbicara berfokus pada tiga karakteristik utama: (1) desain tugas dan dukungan kontekstual, termasuk digital storytelling, CLIL, media sosial, serta tugas berbicara kolaboratif; (2) faktor kognitif dan psikologis, seperti berpikir divergen, fleksibilitas kognitif, motivasi, dan kepribadian; serta (3) inovasi pedagogis dan kolaboratif, meliputi pembelajaran performatif, integrasi teknologi, dan pendekatan pluralingual. Analisis RQ1 menegaskan bahwa kreativitas berbicara diperlukan untuk meningkatkan kefasihan, koherensi, akurasi, dan efektivitas komunikasi. RQ2 menunjukkan bahwa solusi pedagogis kreatif dapat dikembangkan melalui desain tugas inovatif, pemanfaatan teknologi digital, dan lingkungan belajar kolaboratif. RQ3 menemukan bahwa kreativitas berbicara memberikan manfaat signifikan bagi perkembangan linguistik, kognitif, afektif, serta kompetensi abad ke-21, seperti berpikir kritis dan pemecahan masalah. Penelitian ini menegaskan bahwa kreativitas berbicara merupakan fondasi penting dalam pembelajaran bahasa modern dan perlu diintegrasikan melalui strategi pedagogis yang adaptif dan inovatif.